Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Liquid phase oxidation of p-cresol over cobalt saponite - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Topics in Catalysis, 2009)
Liquid phase oxidation of p-cresol was carried out over a Co-saponite catalyst in a temperature and pressure range of 333-393 K and 20-827 kPa, respectively in n-propanol. Co-saponites with varying cobalt content (5-30%) were prepared and screened among which 13% Co-saponite gave the highest conversion of 92% of p-cresol with 92% selectivity to p-hydroxybenzaldehyde without formation of any non-oxidation products.
Keywords: Co-saponite; Liquid phase oxidation; p-Cresol; p-Hydroxybenzaldehyde; XPS

Liquid phase oxidation of p-vanillyl alcohol over synthetic Co-saponite catalyst - Garade, Ajit C.; Biradar, Narayan S.; Joshi, S. M.; Kshirsagar, V. S.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Applied Clay Science, 2011)
Effect of cobalt loading on porosity of synthetic Co-saponite catalysts and on the air oxidation of p-vanillyl alcohol was studied by varying Co content in the range of 5% to 30% using in situ precipitation method. The pore size increased from 1.29 to 3.69 nm indicating a transition from micro to meso porosity, with increase in Co loading from 5% to 30%. The distribution ratio of Co(3)O(4)/CoO phases as estimated from TPR studies, also increased from 0.84 to 1.67 with increase in Co loading from 5% to 13% and remained almost constant (1.7) with further increase in Co loading up to 30%. The highest activity (conversion 55%) and selectivity of 99% to p-vanillin obtained for 13% Co-saponite in p-vanillyl alcohol oxidation was due to the highest distribution ratios of Co(3)O(4)/CoO phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Co-saponite; Cobalt oxide phase ratio; p-Vanillin; p-Vanillyl alcohol oxidation; Porosity transition; Temperature programmed reduction

Lignocellulose-derived platform molecules: an introduction - Shinde, Suhas H.; Hengne, Amol; Rode, Chandrashekhar V. (Recent Advances in Development of Platform Chemicals, 2020)
Fossil feedstocks such as crude oil, natural gas, and coal are formed by natural anaerobic decomposition of buried organisms for a period of more than 650 million years. On the other hand, agrobiomass is quick to grow and becomes a renewable source of chemical and fuel production through processing in a biorefinery.
Keywords: Biomass; Biorefinery Cellulose; Lignocellulose Petrofinery; Platform molecules